(untitled) (Journal of Governance and Development (JGD), 2014)
This study analyzes the politicization of ethnic sentiments in Thailand with particular focus on Deep South of Thailand. It is divided into six parts. The first part examines the relationship between the Thailand’s political system and the minority groups within it. The second part explains the impact of ethnic politics in the Thailand’s political system. The third part discusses the function of ethnic politics. The fourth part examines the organizational base of ethnic politics in the region. The fifth part discusses the patterns of ethnic politics that have developed over the years. And the sixth part synthesizes the theories and practices of ethnic politics in the region. The data for this analysis came from primary and secondary sources, namely newspapers, internet, books, magazines, and journals. Interviews were also conducted. The study found that the politicization of ethnic sentiment was by product of structural inequalities in the socio-political and economic domains of the Thailand’s society which play important role in intensifying conflicts. As a result, the Malay Muslims ethnic group established their own ethnic associations or organizations which are responsible for the development of strong group identification leading to the emergence of secessionist groups in deep south of Thailand that threaten the core values of the Royal Kingdom of Thailand.